Developing cadres of gender specialists in global public health to meet increasing demand - Kalbarczyk, Anna; Banchoff, Katherine; Perry, Kelly; de Boer, Mary; Morgan, Rosemary (Frontiers in Sociology, 2025)
Gender is increasingly prioritized in global health and embedded across the Sustainable Development Goals. This shift has created a demand for gender specialists with skills to integrate gender into research and programs. Most global health professionals lack formal training in gender analysis or integration. Gender is often misunderstood—conflated with sex, focused only on women, or limited to maternal health. Training can equip professionals to address these gaps, improve outcomes, and reduce inequities. We developed the Gender and Health Summer Institute at Johns Hopkins Bloomberg School of Public Health to grow this capacity. Using universal design, the Institute enhances accessibility, inclusivity, and engagement. Our goal: build a global cadre of gender specialists driving more gender-responsive and equitable health programs.